1978
DOI: 10.1111/j.1399-0039.1978.tb01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Mixed Lymphocyte Response in Ankylosing Spondylitis

Abstract: A diminished mixed lymphocyte response was reported by Nikbin et al. (1976) among patients with ankylosing spondylitis, their asymptomatic relatives and also normal controls carrying the B27 antigen. In the present communication, the responses in 48 ankylosing spondylitis patients and 45 controls were examined in mixed lymphocyte cultures tested against a 'standard stimulator' made up of pooled lymphocytes. A significantly diminished response is confirmed among the ankylosing spondylitis patients, but not in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Our results on a larger population sample did not support this association. On the other hand, the low reactivity of the HLA-Bw27 bearing subjects, found by Nikbin et al (1976), but denied by Wee & Daymond (1978), was confirmed by our results.…”
Section: Association Between T-lymphocytesupporting
confidence: 88%
“…Our results on a larger population sample did not support this association. On the other hand, the low reactivity of the HLA-Bw27 bearing subjects, found by Nikbin et al (1976), but denied by Wee & Daymond (1978), was confirmed by our results.…”
Section: Association Between T-lymphocytesupporting
confidence: 88%
“…The function of APCs in SpA has not been systematically examined. A diminished mixed leukocyte response in patients with ankylosing spondylitis and individuals with HLA–B27 has been reported (15, 16), but to our knowledge the cellular basis for this observation remains undefined. Given the consistently defective DC function observed in SpA‐prone HLA–B27/Huβ 2 m–transgenic rats, investigation of DC function in SpA patients seems warranted.…”
Section: Discussionmentioning
confidence: 98%
“…Granulocyte-specific antinuclear antibodies (24) also occur in a small number of patients. Some investigators have found mitogen stimulation and the percentage of T cells in the blood to be abnormally low; others have found them normal (25)(26)(27)(28)(29). While it is possible that antibodies to beta 2 microglobulin in patients with ankylosing spondylitis might also reflect a generalized immunoregulatory defect, a more intriguing possibility is raised by the recent work of Edmonds et a1 (30).…”
Section: Discussionmentioning
confidence: 99%